Heterogeneous clinical and functional features of GRIN2D-related developmental and epileptic encephalopathy - XiangWei, Wenshu; Kannan, Varun; Xu, Yuchen; Kosobucki, Gabrielle J.; Schulien, Anthony J.; Kusumoto, Hirofumi; Moufawad El Achkar, Christelle; Bhattacharya, Subhrajit; Lesca, Gaetan; Nguyen, Sylvie; Helbig, Katherine L.; Cuisset, Jean-Marie; et al. (Brain, 2019)
NMDA receptors are implicated in various neurological diseases. XiangWei et al. identify seven GRIN2D variants associated with developmental and epileptic encep
Gesehen am 28.04.2020